A midiatização da dor: estratégias comunicativas e resistência política - Oliveira, Andressa Cantergiani Fagundes de (2008)
The objective of this dissertation is to examine how the pain and its vestiges - especially the scars and their various metaphors - have been mediatised in recent decades, in various different ways, within itself. In general, what one sees in the Mass Media (especially internet, TV and newspapers) are mere sensationalist approaches of content, that exposes the pain and suffering in an excessive, banal and even fictional way, as displayed in the broad exhibition of the war scenes in Iraq, the terrorist attacks of 9/11 and in the brutal killings of Rio de Janeiro's slums, among others. However, the survey points to some performative experiences, performed, in several countries mainly since 1960, and which became the object of controversy in the media itself and in especialized essays in the Art field (Elkins 1999) and Political Philosophy (Scarry, 1985; Keil, 2004), once , rather than trivialize, chose to test procedures that originate from performances of pain to transform the understanding of power, of art, of life and body as a mediabody. Therefore this research discusses, some of these experiences, having as its core question the primary processes of bodily communication, prior to the systematization of a speech. Contrary to the common sense evidence, and the non specialized-press reiterates, such experiments are not solely related to the pathologies and idiosyncrasies of sadomasochistic artists. Moved, often for reasons of political order such actions question various kinds of limits, mainly related to the principles of bodily communication and the action of a body exposed to specific situations (e.g. terrorism, massacres and power related abuse). As a theoretical framework, in addition to the previously mentioned authors, the research examines the primary communication of the body and its sensitive strategies (Sodré, 2006; Greiner, 2005). As a result this dissertation presents the analysis of the Works of a Brazilian, Claudia Müller, who has discussed through experiences with videodance and performances, the inclusion of art in several society sectors